2000
DOI: 10.1161/01.cir.102.11.1258
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin Antibodies and Recurrent Coronary Events

Abstract: In postinfarction patients, elevated IgG aCL and low IgM aCL antibodies are independent risk factors for recurrent cardiac events. Patients with both elevated IgG aCL and low IgM aCL antibodies have the highest risk. These findings shed additional light on the mechanistic role of aCL antibodies in coronary artery disease in patients without autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 42 publications
1
21
1
2
Order By: Relevance
“…Zuckerman, et al 4) reported that the rates of thromboembolic events and myocardial reinfarction in patients with acute MI were significantly higher in aCL-positive patients than in the aCL negative group. The largest study on this issue was recently reported by Bili, et al 29) who studied 1150 AMI patients. They suggested that elevated aCL-IgG and low aCL-IgM antibodies were independent risk factors for recurrent cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Zuckerman, et al 4) reported that the rates of thromboembolic events and myocardial reinfarction in patients with acute MI were significantly higher in aCL-positive patients than in the aCL negative group. The largest study on this issue was recently reported by Bili, et al 29) who studied 1150 AMI patients. They suggested that elevated aCL-IgG and low aCL-IgM antibodies were independent risk factors for recurrent cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anticardiolipin antibodies in the general population is reported to be between 1% and 9% [7,8]. Anticardiolipin antibodies were shown to be an independent risk factor for MI and recurrent events [9,10]. In the present study, we evaluated the yield of thrombophilia screening among young patients with MI and examined the relationship between the presence of thrombophilia and patients' traditional risk factor profile.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, some authors 3,10 have found that aPL antibodies after MI are a risk factor for recurrent events, although these results have not been verified by others 11,12 . In addition, anticardiolipin antibodies in healthy men have been shown to confer a twofold increased relative risk for MI 2 .…”
Section: Discussionmentioning
confidence: 90%